Solving cold cases: The importance of new identification techniques in old cases of forensic anthropology - Gabriela Araujo dos Santos; Talita Lima de Castro Espicalsky; Leticia Regina Alfaia Custódio; Melina Calmon Silva; Eugenia Cunha (Forensic Science International: Reports, 2024)
Scientific and technological developments experienced by forensic sciences have increased the possibility of human identification. Forensic anthropology has developed worldwide and has made significant progress in Brazil in the last 10 years. This context has allowed forensic medicine institutes to use new techniques to resolve cold cases of human identification. This work aimed to report the methodology, development, and partial results of the LAFOL Identifies Operation, carried out at the Forensic Anthropology and Forensic Dentistry Laboratory (LAFOL) of the Medico-Legal Institute of Porto Velho. We carried out a multidisciplinary expert approach on human skeletal remains archived over the last 20 years to identify these individuals using current scientific methods. Eighty-one cold cases of skeletonized and/or mummified human skeletal remains were reanalyzed; they were archived in the LAFOL Laboratory collection as unidentified. Anthropological analyses showed that the collection is predominantly composed of adult individuals (86.4%), between 21 and 39 years old (55.6%), and males (62.9%). In the human skeletal remains identified, forensic anthropology played a key role in the case screening process. We expected that the results presented in this work will inspire other Medico-Legal Institutes in Brazil and worldwide to establish task forces for the reanalysis of cold cases in their institutes, promoting new forensic dentistry and anthropological comparisons and collecting biological samples to feed the database of genetic profiles of missing persons.